Psychophysiological treatment of chronic tinnitus: A review. (13th January 2022) - Czornik, Manuel; Malekshahi, Azim; Mahmoud, Wala; Wolpert, Stephan; Birbaumer, Niels
Abstract: Subjective chronic tinnitus consists of a more or less continuous perception of sound in the absence of a corresponding acoustic source, which can lead to various psychological problems like depression, anxiety, attentional deficits and sleep disturbances. The prevalence is 10%–15% of the general population. Various therapy and management options have been proposed, but outcomes vary, and no generally accepted cure exists. In this review, the coherence of the most frequently used aetiological models shall be evaluated, and the efficacy of several treatment options will be discussed. With respect to tinnitus treatments, we focus on controlled studies and meta‐analyses. Although there are some therapies that outweigh placebo effects such as cognitive behavioural therapy, neurofeedback or neuromodulation techniques, they mainly target secondary symptoms and not the tinnitus tone itself. Furthermore, positive treatment effects only seem to last for a limited period of time. We conclude that long‐lasting combination therapies such as neurofeedback of auditory cortex inhibitory EEG signatures, cognitive therapy and sound‐tactile stimulation may provide more efficient outcomes if they target the intensity of the tinnitus tone itself and not only secondary psychological symptoms.